Verna Lalbeharie joins EdTech Hub as incoming Executive Director - Hub, EdTech (EdTech Hub, 2021)
We are excited to announce that Verna Lalbeharie is joining EdTech Hub as the incoming Executive Director. A native of South Africa, now living in North Carolina (USA), Lalbeharie brings not only 25 years of EdTech expertise to the role, but also a career-spanning commitment to evidence-building in education technology to create a more equitable future for all students. “When…
KerkoCite.ItemAlsoKnownAs: 2405685:GWTBTPXG
Keywords: _EdTechHub_Output

Highlights from EdTech and Covid-19: Lessons learned, future plans - Team, EdTech Hub (EdTech Hub, 2021)
On March 2nd EdTech Hub brought together education leaders, including teachers, program managers and policymakers, to reflect on a year of EdTech and Covid-19, discuss the lessons learned so far and consider how we can prepare for the future. Over 200 people joined from around the world for a lively and thought-provoking discussion. Speakers included: Helen Grant MP, UK Prime…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707919 2405685:UKK52XU7
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Open educational resources - EdTech Hub (EdTech Hub, 2020)
As part of our COVID-19 response, the EdTech Hub is collecting and facilitating access to open educational resources (OER). Open educational resources are teaching, learning and research materials that are made freely available for anyone to access and re-use. These documents are currently stored on Google Drive (no sign-in required). We will add additional distribution […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707762 2405685:8HVQCGY9 2405685:XFLWPJ5R
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Call for ideas for EdTech responses to coronavirus (COVID-19) - EdTech Hub (EdTech Hub, 2020)
UPDATE: The call is now closed We’ve opened a sub-window in partnership with UNHCR for refugee related ideas that respond to COVID-19 school closures. Find full details here. Our call for ideas to respond to the learning emergency caused by COVID-19 school closures is now closed. We have been delighted and overwhelmed by the huge number […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707758 2405685:CZ9F7VZ2
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707884 2339240:6XDHWICN 2405685:7FQR6GZK 2405685:Y22H6PQD
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Hub: Resources from other organisations - EdTech Hub (EdTech Hub, 2020)
Response efforts and collated resources Global Partnership for Education (GPE)’s response and resources INEE (Inter-Agency Network for Education in Emergencies) collated resources organised by theme COVID-19 ICT4E resources from mEducation Alliance members UNESCO’s response to COVID-19 including information about distance learning tools and national platforms UNHCR’s guidance on distance learning World Bank resources to help […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707760 2339240:6Q943EP5 2405685:Y76SNV85
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Designing for Scale: Understanding design principles and learning process for a personalised learning platform in Kenya - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596448 ZenodoArchiveConcept: 5596447 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0053 2405685:27K3U5W4

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596872 ZenodoArchiveConcept: 5596871 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0054 2405685:4N5VUGJG

The Impact of a Tech-Supported, School-Based TCPD Model on Learning Outcomes in Tanzania - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596877 ZenodoArchiveConcept: 5596876 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0056 2405685:PFMSZZ8N

Optimising Messaging to Promote Returns to School in Ghana for Marginalised Learners - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596883 ZenodoArchiveConcept: 5596882 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0058 2405685:DMVKGJWQ

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596885 ZenodoArchiveConcept: 5596884 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0059 2405685:7TUWEUKZ

Cost-Effective Technology Approaches to Improve Education Outcomes for Girls: Learning from 41 Girls’ Education Challenge projects - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596887 ZenodoArchiveConcept: 5596886 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0060 2405685:8ZWX2JI5

EdTech Systems Research - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596889 ZenodoArchiveConcept: 5596888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0061 2405685:MDEEA895

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
ZenodoArchiveID: 4709700 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709700 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5032936 10.5281/zenodo.5142392 10.53832/edtechhub.0094 2405685:G9DHSZ57 2405685:HL6BNMQZ
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Conceptual Framework for Monitoring Hybrid Learning Delivery Toward Long-Term System Strengthening and Resilient Education Systems - UNICEF; EdTech Hub (UNICEF, EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5826262 10.53832/edtechhub.0073 2405685:3EQU9ZAN
Keywords: F: Helpdesk response; _r:AddedByZotZen

Monitoring Hybrid Learning: A Short Guide - UNICEF; EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5826252 10.53832/edtechhub.0072 2405685:NHNPTFBW
Keywords: F: Helpdesk response; _r:AddedByZotZen

Operational Guide for Monitoring Hybrid Learning Delivery Toward Long-Term System Strengthening and Resilient Education Systems - UNICEF; EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5826264 10.53832/edtechhub.0074 2405685:P59N3JKT
Keywords: F: Helpdesk response; _r:AddedByZotZen

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
ZenodoArchiveID: 4486906 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4486906 2339240:NTGE2FPC 2405685:DU497D8A 2405685:HCV5X9YJ
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749654 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749654 2405685:39XPD5EM 2405685:QZ2FJC4E
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

O Efeito da COVID-19 na Educação em África e Suas Implicações para a Utilização da Tecnologia Um Inquérito sobre a Experiência e as Opiniões de Educadores e Especialistas em Tecnologia - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749656 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749656 2405685:XSK5P8VC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTechTools Relaunched with TVET Resources - EdTech Hub; Generation Unlimited (EdTech Hub, 2021)
EdTechHub, Generation Unlimited (GenU), UNESCO and UNESCO-UNEVOC have joined forces to relaunch EdTechTools (formerly the Tools Database): a global repository of education technology tools and platforms designed to help decision makers at all levels in the global education and training community find resources that facilitate and support remote learning. More than a year after the world experienced an education disruption…
KerkoCite.ItemAlsoKnownAs: 2405685:HNAI38V8
Keywords: _EdTechHub_Output

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
ZenodoArchiveID: 5596875 ZenodoArchiveConcept: 5596874 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5896640 10.5281/zenodo.6504993 10.53832/edtechhub.0055 2405685:HT8ZGKAB 2405685:QAH4K4D6 2405685:SE5JPCX2
Keywords: HLR3; _r:AddedByZotZen

Curated Tools for Teacher Continuous Professional Development - Hub, EdTech (EdTech Hub)
EdTech Hub has created curated lists of teacher professional development (TPD) tools along with evidenced-based advice on how to effectively use them. Because, of course, it’s not only which tool you choose, but how you use it that will determine whether it will lead to better teaching and learning.
KerkoCite.ItemAlsoKnownAs: 2405685:M4R4WE38 2486141:43N7BJSK

Explore EdData Tools - Hub, EdTech (EdTech Hub)
Crowdsourcing Data Technologies for Education in Emergencies
KerkoCite.ItemAlsoKnownAs: 2405685:6T7DNXRX 2486141:TFRMMCMG

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Education system management / EMIS / education data – EdTechTools - EdTech Hub (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:YGEJ34XE 2405685:GTJ3R8F6 4656463:ZZTLJD2P

Education system management / EMIS / education data – EdTechTools - EdTech Hub
KerkoCite.ItemAlsoKnownAs: 2339240:7HF4AHXE 2405685:7STESA5R

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub (EdTech Hub)
This systemic mixed-methods study will build evidence on the most feasible approach to GIS-supported teacher allocation in Sierra Leone and assess the impact of this approach on teacher retention and attendance. Discover more...
KerkoCite.ItemAlsoKnownAs: 2405685:IL6PS236 2486141:RKFMTQTQ

EdTech for Digital Personalised Learning - EdTech Hub (EdTech Hub, 2022)
Evidence on how technology can be used to maximise the effectiveness of personalised learning and teaching at the level of the student.
KerkoCite.ItemAlsoKnownAs: 2339240:ZCFHC5VL 2405685:RDDSSH2L

EdTech Interventions Database - EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3P7HKD8E 2405685:38GA4ZAF

EdTech companies in Sub-Saharan Africa - EdTech Hub (Airtable, 2020)
Explore the "EdTech companies in Sub-Saharan Africa (see https://tabsoft.co/338AGht for visuals)" view on Airtable.
KerkoCite.ItemAlsoKnownAs: 2339240:J7JR8C2K 2405685:64SY5VBN

EdTech Hub Rapid Scans - EdTech Hub
KerkoCite.ItemAlsoKnownAs: 2339240:PJ3723SV 2405685:3SDUBZRG

Focus country: Bangladesh - EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R62Y25DW 2405685:IFIR3QC9

Value for Money Policy and Procedure - EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:DLHKFUVC 2405685:V6TUMYRQ

Research - EdTech Hub (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:S7VNMT74 2405685:SGN72ZXM

Using laptops to distribute video sign language lessons to deaf children in Pakistan - EdTech Hub
We tested different EdTech interventions to find out which ones would be most suitable for providing distance learning for deaf children.
KerkoCite.ItemAlsoKnownAs: 2339240:W5IM27KA 2405685:PMP2QQJV

Our Strategy, Part 1: Empowering decision-makers with evidence to improve learning for all - EdTech Hub (EdTech Hub, 2022)
For the last five months, EdTech Hub has been exploring and refining our strategy for advancing evidence in EdTech for low- and middle-income countries. We invite you to explore our thinking for how we will carry out this mission within our context and in partnership with the global EdTech community. Verna Lalbeharie, Executive Director Acknowledgements Thank you to all of…
KerkoCite.ItemAlsoKnownAs: 2339240:AMV4DLSG 2339240:VADKXL3E 2405685:5ZYSLE8K 2405685:TLLYS3BK

Our Strategy, Part 2: Deep dive into our approach, focus countries, and theory of change - EdTech Hub (EdTech Hub, 2022)
In Part 2 of our strategy, we go deeper into EdTech Hub’s integrated approach to how we work, where we work, and how that comes together with our topics to inform our theory of change. Verna Lalbeharie, Executive Director The EdTech Hub integrated approach We do research because it is imperative to build deep quantitative and qualitative insight regarding how…
KerkoCite.ItemAlsoKnownAs: 2339240:7DMT34XG 2339240:TFZQRG6B 2405685:8AMLEXFH 2405685:TFAGI64Q

Results – Rapid Scans – The EdTech Hub - EdTech Hub (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4MLKCQH6 2405685:M78IF9TS 4656463:IAPZ4MLA

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - EdTech Hub (2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
KerkoCite.ItemAlsoKnownAs: 2405685:EVU4DEWP 4042040:T3S2AEMN

EdTech Hub Strategy: Mitigating the impact of COVID-19 on equitable education access and learning - The EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Z9NRHELL 2405685:ID5A529H

EdTech Hub Quarterly Report October to December 2020 - EdTech Hub Team (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:5X7TAC2B 2405685:5X7TAC2B;10.5281/zenodo.4354796

Developing a teacher-focused theory of change for technology-enhanced teaching and learning - EdTech Hub Team (2021)
Internal Brief
KerkoCite.ItemAlsoKnownAs: 2405685:2SL6PDSS

Effective Assessment and Progress Monitoring in an Online Environment: A Study in Six Countries - T4 Education; EdTech Hub (EdTech Hub, 2022)
The study was undertaken in six countries – Bangladesh, India, Nigeria, Pakistan, Philippines, and South Africa. The data collection involved focus group discussions with two held in each country..
KerkoCite.ItemAlsoKnownAs: 2339240:PA9TD6UB 2405685:E66UZCLZ

Designing and monitoring distance teaching and learning interventions: A guide for projects and implementers - Girls' Education Challenge; Fund Manager; EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:58CZ6GI8 2405685:ATJRX6DV

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessey, Sarah; Jordan, Katy; Wagner, Daniel; EdTech Hub Team (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:P8FGXBPB 2405685:F8WM8674
Keywords: ⛔ No INSPIRE recid found

Usability Testing of a Mobile-based Learning Management System for Teacher Continuous Professional Development in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Haßler, Björn; Proctor, Jamie; EdTech Hub (The International Journal of Education and Development using Information and Communication Technology, 2023)
The last two decades have seen the growing adoption of mobile devices to enhance the quality of teachers' continuous professional development (TCPD) in low-income countries. Using mobile devices, typically not designed for educational use, presents new usability challenges, preventing teachers from effectively accessing learning materials in learning management systems (LMS). Therefore, it is important to test usability to improve the delivery of TCPD via mobile devices. This study evaluated the usability of TCPD-focused mobile-based LMS accessed via a mobile web browser and mobile app. The evaluation used a hybrid think-aloud method involving 63 teachers from 12 schools in Tanzania. Half of the schools were evaluated using a concurrent think-aloud method, and the other half using a retrospective think-aloud method. The study found that teachers encountered many usability problems in using the mobile app compared to those who accessed the LMS via mobile web browsers. The study also found usability flaws in the registration and login process, poor language translation, technical errors, and issues with quiz questions. These findings show the importance of user testing, even for well-developed LMS, such as Moodle. Additionally, this work provides useful guidance for those who want to implement mobile learning via an LMS in low-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:ZTWSB6CB 2405685:L5AY2YZI
Keywords: ⛔ No DOI found